Out of the blue : a new blue Lymanopoda butterfly from the páramo of northern Colombia raises questions about disjunct distributions (Lepidoptera: Nymphalidae, Satyrinae) - Pyrcz, Tomasz W.; Boyer, Pierre; Garlacz, RafaŁ; Fåhraeus, Christer; Andrade-C, Miguel Gonzalo; Bálint, Zsolt; Mahecha-J, Oscar (Zootaxa, 2025)
A new, striking species of satyrine butterfly, Lymanopoda chysquyco sp. nov. (Nymphalidae, Satyrinae, Satyrini, Pronophilina) is described from the Páramo de Guerrero, the northern extremity of high-altitude grasslands in the Colombian Eastern Cordillera. Among approximately 70 known Lymanopoda species, only five exhibit blue colour on the upperside of their wings, with no evidence of close relationships among them. The new species superficially resembles L. samius Westwood which occurs parapatrically at slightly lower elevations and belongs to a distantly related lineage within the genus. Remarkably, external morphology and male genitalia suggest a strong similarity of the new species to L. hazelana found in southern Ecuador and northernmost Peru - over 1300 km away. Molecular analysis using COI barcoding confirms that L. hazelana and a few other closely related species also found in southern Ecuador are the closest known relatives of L. chysquyco sp. nov. This substantial geographic disjunction is unlikely to be a sampling artefact, as intermediate páramo regions of the Eastern and Central Colombian Cordillera and central Ecuador have been extensively surveyed. The origin of L. chysquyco sp. nov. in northern Colombia remains unclear, and two possible scenarios - longdistance dispersal or vicariance accompanied by large-scale extinction in intervening areas - are considered.
Keywords: Andes; COI barcoding; Lymanopoda chysquyco sp. nov.; phylogenetic relationships; Pronophilina; structural colours; taxonomy